Application of islamic business ethics in online selling and buying transaction - Rifda Nabila (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
Basically, there are many things can affect Customer Satisfaction, one of which is the application of business ethics. In Islam, buying and selling transactions are something permissible as long as the conditions in accordance with Islamic Shari'a can be fulfilled. Islamic Business Ethics guarantees business people, both of business people, business partners, and consumers will benefit from each other in a particular business transaction. This study aims to analyze the influence between the variables of Islamic Business Ethics on the Customer Satisfaction variable, and (2) the influence of the Customer Satisfaction variable towards the Word of Mouth variable. The sample of this study is 200 respondents. The data analysis technique used Partial Least Square (PLS). Based on the results of the study it can be concluded that the Islamic Business Ethics Variable consisting of Free Will and Benevolence has a positive influence on Customer Satisfaction and the Customer Satisfaction variable has a positive influence on Word of Mouth. While the Unity, Equilibrium, and Responsibility variables do not affect Customer Satisfaction.